El miedo al judío en la España de la Edad Media - Enrique Cantera Montenegro (Estudios de Historia de España, 2016)
This study examines the fi gure of the Jew as a possible instigator of fear in the medieval Christian Hispanic society; one that is intimately related to the image of the Jew which emanates from Civil and Canon law enacted throughout the Middle Ages. By analysing the various causes of fear induced by the Jews, a distinction will be made between factors causing physical fear, which probably had a more popular and irrational origin, even if these may have been induced from within intellectual circles, and those producing spiritual fears of a more intellectual and rational nature.